FORMULATION AND CHARACTERIZATION OF INSTANT POWDER COMBINATION OF MILK, YOLK AND TEMULAWAK (Curcuma xanthorriza Roxb) TO PREVENT STUNTING - Sutiswa, Shandra Isasi; Aji, Nur (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Through its health transformation program, the Ministry of Health has replaced giving biscuits as additional food to toddlers and pregnant women to prevent stunting with animal protein made from local food. Milk and eggs are local food sources of animal proteins that can be processed into nutraceuticals. Another cause of stunting is lack of appetite, nausea, and vomiting in children during pregnancy. Temulawak is a traditional medicine that can improve appetite. A combination of milk, yolk, and temulawak can be formulated for nutraceutical preparation. This study aimed to develop and test the characteristics of instant powder combinations of milk, yolk, and temulawak to prevent stunted growth. The laboratory experimental method was used in this study. The formula was prepared by mixing temulawak extract granules with powder obtained from the freeze-drying process of milk and yolk. There were 3 variations of the combination concentration with a ratio of milk : yolk : temulawak, F1 (40:2:3), F2 (50:3:2), and F3 (60:4:1). The results of the research showed that all formulas had physical characteristics in the form of light yellow powder with a typical ginger aroma, particle size between 119.66–120.39µm, angle of repose between 36.40–44.46°, flow rate between 1.32–1 .34g/sec, specific gravity between 0.44-0.47g/mL, tap density between 0.62–0.68g/mL, compressibility between 13.00-13.33%, pH between 6.45–6, 48, dispersibility time between 02.14 – 02.17 minutes and water content between 3.48 – 4.93% according to SNI-01-2970-2006 instant milk powder ...